Shinohata : - Dore, Ronald P. (University of California Press, 1978)
Ronald Dore offers the reader insight into the changing rural life of Japan in this fascinating study of a village some 100 miles from Tokyo where he lived first in 1955 and again in the early 1970s. A new Afterword reports on the acceleration of change to a once self-sufficient community most of whose young men now commute to city jobs instead of working the land.